Becoming Neolithic in words, thoughts and deeds. (February 2019) - Mithen, Steven
How did people come to 'think Neolithic'? While there has been considerable progress in reconstructing the environmental, economic, technological and social changes associated with the transition from mobile hunter-gathering to sedentary farming and herding communities, we remain limited in our understanding of how Neolithic culture in its most profound sense arose. I suggest that the formation of new words required for that new lifestyle was as much a driver as a consequence of the Neolithic transition, illustrating this with a sample of Neolithic innovations from the southern Levant that appears likely to have required new words. Such words, I argue, helped to establish new concepts in the mind, shaped thought, influenced perception and ultimately the human deeds in the world that left an archaeological trace.